Pemeriksaan Dini Kondisi Kesehatan Lansia dan Sosialisasi Perawatan Lansia terhadap Keluarga di Desa Kalibuntu, Kraksaan, Probolinggo - FITRIYAH, LAILATUL; Malihatul Lu’lu’a; Qurrotul Aini; Silviana Dewi (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
The typical environmental conditions of the coast of Kalibuntu Village which are not kept clean, as well as frequent tidal floods in this area make the level of environmental health in Kalibuntu Village problematic. The flood caused the water in the rivers and wells of the residents to become cloudy, accompanied by the spread of garbage everywhere. In terms of elderly health, residents rely on the presence of the polindes as the fastest and easiest access to health services that are closest and financially affordable. From our collaboration with the Polindes and the Posyandu service for the elderly, the elderly in this village are quite vulnerable to respiratory diseases, stroke, cholesterol, gout, and high blood pressure. This disease is triggered by unhealthy environmental conditions and lack of ability to meet daily nutritional and nutritional needs. To help the elderly's health efforts, it is inseparable from the role of the family. From a societal perspective, the family is the basic system by which health and care behaviors are regulated, practiced, and carried out. With this condition the community service team decided to carry out a series of social activities with the aim of 1) Compiling a set of social activities to conduct an Early Examination of the Health Conditions of the Elderly, and 2) Compiling a set of social activities to conduct Socialization of Elderly Care, "Healthy Elderly", to Families elderly. This activity is expected to provide benefits in the form of: 1) Meeting the need for factual and "by the time" data regarding health conditions and health problems of the elderly, 2) Data can be used by health workers and local health policy makers to take anticipatory actions to avoid problems greater health care or responsive actions to immediately address the health problems of the elderly, 3) Socialization activities are intended to provide education for elderly families about the importance of alertness and knowledge of the health of the elderly, 4) Socialization activities are expected to be able to significantly ease the task of health workers and caregivers health policy in Kalibuntu Village, Kraksaan, Probolinggo.